2016
DOI: 10.1126/science.aad9195
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 broadly neutralizing antibody precursor B cells revealed by germline-targeting immunogen

Abstract: Induction of broadly neutralizing antibodies (bnAbs) is a major HIV vaccine goal. Germline-targeting immunogens aim to initiate bnAb induction by activating bnAb germline precursor B cells. Critical unmet challenges are to determine whether bnAb precursor naïve B cells bind germline-targeting immunogens and occur at sufficient frequency in humans for reliable vaccine responses. We employed deep mutational scanning and multi-target optimization to develop a germline-targeting immunogen (eOD-GT8) for diverse VRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
593
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(612 citation statements)
references
References 35 publications
16
593
3
Order By: Relevance
“…We observed that clonal lineages were shared among many tissues ( Figures 5C, 6, and 7) but only ~45% of these lineages had members found in peripheral blood (Table 1). Given recent work aimed at stimulating germline precursors of broadly neutralizing antibodies and quantifying those responses (29)(30)(31), data from the present study suggest that sampling of blood alone may not be able to detect all vaccine-elicited responses.…”
Section: Discussionmentioning
confidence: 74%
“…We observed that clonal lineages were shared among many tissues ( Figures 5C, 6, and 7) but only ~45% of these lineages had members found in peripheral blood (Table 1). Given recent work aimed at stimulating germline precursors of broadly neutralizing antibodies and quantifying those responses (29)(30)(31), data from the present study suggest that sampling of blood alone may not be able to detect all vaccine-elicited responses.…”
Section: Discussionmentioning
confidence: 74%
“…While Envs have been designed for reacting with UCAs of heterologous bnAb lineages (85, 87, 88), we have taken the approach of identifying, in selected HIV-1-infected individuals who make bnAbs, the natural sequence of Envs that were implicated in bnAb lineage maturation in order to select sequential immunogens. While such immunogens are designed for the UCA and intermediate antibodies of one particular bnAb lineage, they hold promise for inducing bnAb lineages in multiple individuals because of the remarkable conserved usage of V H and V L genes of bnAbs and the restricted nature of antibody motifs for many bnAb types, particularly for the gp41 membrane proximal region (89), the CD4 binding site (42) and the V1V2-glycan site (15, 41, 55, 56).…”
Section: B Cell Lineage Immunogen Designmentioning
confidence: 99%
“…A germline-targeting, gp120 outer domain immunogen (OD-GT8) on self-assembling nanoparticles, was able to activate VRC01-class precursors, select productive mutations, create a pool of memory phenotype B cells and induced antibodies that showed characteristics of the VRC01-class bnAb, in a germline reverted VRC01 Hchain knock-in mouse model (VRCO1 gH) 102 ; as well as isolate VRC01-class precursor na€ ıve B cells from HIV-uninfected donors. 103 Furthermore, administration of boosting immunogens (BG505 core-GT3 nanoparticle (NP) and BG505 SOSIP-GT3 trimer) drove the maturation of eOD-GT8 60-mer primed B cells toward VRC01-class bnAb and induced broad neutralization of near-native (N276A) viruses and weak neutralization of a fully native virus in VRC01 gH mice. 104 These data showed that B-cell lineage vaccine design has the potential to induce bnAb.…”
Section: Eliciting Broadly Neutralizing Antibodies Through Immunizationmentioning
confidence: 99%